Bilingual education teachers' perceptions of the educational climate and policies in the United States and Spain - Miguel Fernández Álvarez; Jesús Paz-Albo; Aránzazu Hervás-Escobar; Amanda Montes (Universidad Complutense de Madrid, 2021)
Access to high-quality bilingual education is critical and has evolved in many different ways during the last decades. Given recent efforts to enhance bilingual education, it is important to examine the perceptions of the current education workforce who serve students in bilingual education programs. A hundred and sixty-four bilingual education professionals from Spain and the U.S. participated in the research. They completed a questionnaire about the effect of educational climate and policies in their own countries. Findings show that teachers from Spain rate bilingual education higher than teachers from the U.S. There are significant differences in their general perceptions and insights about resources, collaboration, students, parents and community. Being proficient in two languages seems to have a positive effect on two categories: general perceptions and perceptions about parents. Our findings also suggest that the years of teaching experience influence their responses and there is a need for more professional development in both countries.